Visual Research of Global Orphan Drug from a Bibliometric Perspective - Wen X; Jin G; Wu C (Drug Design, Development and Therapy)
Xiaoya Wen,1,* Guangzhi Jin,2,* Chunxing Wu3 1Department of Pharmacy, The Fourth People’s Hospital of GuiYang, Guiyang, Guizhou Province, 550007, People’s Republic of China; 2Department of Hemodialysis Room, The Second People’s Hospital of Guizhou Province, Guiyang, Guizhou Province, 550001, People’s Republic of China; 3Department of Pharmacy, Binzhou Central Hospital, Binzhou, Shandong Province, 251700, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chunxing Wu, Department of Pharmacy, Binzhou Central Hospital, Binzhou, Shandong Province, 251700, People’s Republic of China, Email yurenchunxing@126.comObjective: This study analyzes the current research landscape and trends in orphan drug development, providing insights for future advancements in the field.Methods: Gathering pertinent material from the China National Knowledge Infrastructure (CNKI) and Web of Science databases. Microsoft Office Excel 2017, VOSview 1.6.20, and CiteSpace 6.3R2 were utilised to summarise the present research state and offer insights into research hotspots in the domain of orphan drugs.Results: A total of 3598 research papers were included, with Chinese research showing a continuous upward trend, while international research has entered a slow development stage. The field of orphan drug research has formed a sizable research team, and cooperation between international institutions is relatively mature. Meanwhile, the United States and the United Kingdom have strong influence in this research field, while China lacks international cooperation. The research focus in this field mainly involves the development and clinical application of orphan drugs, and domestic and foreign research also has its own emphasis. Maintain consistency in clinical trials and medication support for orphan drugs both domestically and internationally; And foreign research has obvious advantages in the development of orphan drugs. Keyword emergence research indicates that the clinical accessibility and regulatory approval of orphan drugs have become a prominent issue of interest both nationally and globally.Conclusion: This study systematically summarises and examines the current research status and emerging trends in the global orphan drug sector by analysing relevant literature from 2000 to 2024 through bibliometric methods. It further delineates the similarities and differences in orphan drug research domestically and internationally, offering valuable references for future investigations in this domain.Keywords: orphan drug, rare disease, bibliometrics, medication guarantee, orphan drug development